PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH BRITAMA STUDI KASUS PADA PT. BRI (PERSERO) TBK, CABANG MANADO PINAESAAN - Sinaga, Nova Uli; Sumampouw, Harry; Keles, Dantje (Sam Ratulangi University, 2014)
This study is based on the thought of several factors that affect customer satisfaction with the Bank. Competition in the banking business world is very tight, with a large number of banks and their varying competing products or services offered. Currently the bank takes effort to get potential customers and retain existing customers. By understanding the needs, wants and demands of customers, by providing quality service banking firms, banks must meet at least five criteria of quality of service is often called RATER so can create loyal customers, namely reability, assurance, tangible (physical evidence), empathy (communication), and responsiveness (quick response) to meet the criteria of the quality of service it will be creating customer satisfaction. The event is held at. BRI (Persero) Tbk, Branch Pinaesaan Manado, with the aim to determine influence of service quality on customer satisfaction BritAma. In addition this study are expected to be input to the leadership and employees of PT. BRI (Persero) Tbk, Branch Manado Pinaesaan and a contribution in solving the problem. Research was conducted by the method of observation, interviews, and questionnaires were addressed to the 50 respondents, of which each respondent had to fill out a list of questions. The results of this study to answer the hypothesis; There is a significant relationship that affects service quality on customer satisfaction, with significant power shows that the determinants of satisfaction or customer satisfaction BritAma depends on these factors are very strong worth the balance of other factors. The results of the t test or correlation thus factors that affect customer satisfaction BritAma is significant at confidence level. Key words: quality of service, customer satisfaction